The costing units of the 6 Rs of Marketing (Costos y Gestión, 2020)
The advance of the changes caused by the behavior of the actors in the so-called “New Economy” has impactedon decisions and marketing models. These changes have been picked up by authors in a fundamentalarea of business administration, such as “Marketing”. Now, the key to the change in the development of theso-called “relational marketing” has been to accept that all business management models, on which businesshas advanced, have been based on products. While, from the shortening of life cycles and their ephemeralexistence in the markets, the commercial perspective is reorienting itself to build and consolidate the relationshipwith the client or the segment to which it belongs.Based on the topics of this new perspective, developed by Pablo Fernández in his book The 6 Rs of Marketing:Six proven strategies to monetize his client portfolio, it is possible to structure a cost information platform tofacilitate the commercial management of business with this new approach.The main objective of this paper is to propose the new costing units that will have to be defined, to assign thecosts of the actions in each of them and to allow the business manager to make decisions about these keyfactors of the model, considering it as a second complementary level of product-based marketing.
Keywords: Relational Marketing; Marketing Costs; 6R; New Economy